Efektivitas Penerapan Pemenuhan Proses Penyidikan Perkara Anak di Kepolisian Daerah Bali - I Putu Gde Asmara Perdana; Luh Nila Winarni; Cokorde Istri Dian Laksmi Dewi (Penerbit Goodwood, 2023)
Purpose: The purpose of this study was to determine and analyze the effectiveness of the application of the fulfillment of the case investigation process of children in the Bali Regional Police. The delinquency of children, which they sometimes considered normal, often caused these children to commit crimes that violated the law. As a child in conflict with the law, often the child's rights are not protected. The majority of children in conflict with the law claim to have experienced acts of violence while at the police station. Methodology: In this research, a sociology of law approach is used, meaning that it examines issues raised with facts supported by a juridical approach. Results: The results of the study show the effectiveness of the diversion process in which perpetrators and victims meet face to face, internationally referred to as